2007
DOI: 10.1016/j.ydbio.2007.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Pescadillo is required for Xenopus laevis eye development and neural crest migration

Abstract: Pescadillo is a multifunctional, nuclear protein involved in rRNA precursor processing, ribosomal assembly, and transcriptional regulation. Pescadillo has been assigned important functions in embryonic development and tumor formation. We previously identified pescadillo as a potential downstream target of non-canonical Wnt-4 signaling. Here we have investigated for the first time the function of the Xenopus laevis homolog of pescadillo during early embryogenesis on a molecular level. Loss of function analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
81
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(91 citation statements)
references
References 49 publications
9
81
0
1
Order By: Relevance
“…32,[61][62][63][64]66 Linear heart tube formation ␤-catenin required for cell-cell contact Supports cell adhesion 59,77,88,89,92,93 ; required for morphogenesis 87,89,95 OFT morphogenesis Required for septation (CNCCs) [103][104][105] Required for cytoskeleton formation and cell-cell interactions 77,[106][107][108][109][110][111] Cardiac looping Required (zebrafish) 98 Not known…”
Section: Disclosuresmentioning
confidence: 99%
“…32,[61][62][63][64]66 Linear heart tube formation ␤-catenin required for cell-cell contact Supports cell adhesion 59,77,88,89,92,93 ; required for morphogenesis 87,89,95 OFT morphogenesis Required for septation (CNCCs) [103][104][105] Required for cytoskeleton formation and cell-cell interactions 77,[106][107][108][109][110][111] Cardiac looping Required (zebrafish) 98 Not known…”
Section: Disclosuresmentioning
confidence: 99%
“…The pes gene was originally identified in a zebrafish mutant characterized by major axis defects, small eyes and early embryonic lethality . Both in vitro and in vivo, disruption of pes has been reported to induce a p53 response (Gessert et al, 2007;Rohrmoser et al, 2007). We therefore undertook an analysis of pancreatic development in pes mutant and morphant embryos.…”
Section: Loss Of Sbds Is Associated With a Broad Change In Ribosome-rmentioning
confidence: 99%
“…It has been shown that pescadillo could immortalize or transform some kinds of mammalian cells [15,16]. Our previous researches and other investigators' researches showed that PES1 was overexpressed in many kinds of human cancer such as malignant astrocytomas and glioblastomas [6], breast cancer [16][17][18], prostatic cancer [19,20], head and neck squamous cell cancer [21], colon cancer [22], ovarian cancer [23], neuroblastoma [24] and gastric cancer [25]. These results suggest that PES1 may play an important role in tumor progression.…”
Section: Introductionmentioning
confidence: 99%